2014
DOI: 10.1186/1471-244x-14-134
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency is common in psychogeriatric patients, independent of diagnosis

Abstract: BackgroundPrevious studies have found an association between psychiatric disorders and vitamin D deficiency, but most studies have focused on depression. This study aimed to establish the prevalence of vitamin D deficiency in elderly patients with a wider range of psychiatric diagnoses.MethodThe study included elderly patients (>64 years) referred to a psychiatric hospital in Northern Norway and a control group from a population survey in the same area. An assessment of psychiatric and cognitive symptoms and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 61 publications
4
23
1
Order By: Relevance
“…However, there is evidence to suggest that vitamin D among people with psychosis is correlated with the season of blood sampling (Belzeaux et al, 2015;Berg et al, 2010;Crews et al, 2013;Grønli et al, 2014;Lally et al, 2016;Zhu et al, 2015) and parathyroid hormone levels (Bergemann et al, 2008;Rey-Sánchez et al, 2009;Schneider et al, 2000), the latter being negatively correlated to vitamin D. What this review highlights are a multitude of variables that have been found to not significantly correlate with vitamin D within the patient population including but not limited to: BMI, age, gender, smoking, duration of illness and GAF score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is evidence to suggest that vitamin D among people with psychosis is correlated with the season of blood sampling (Belzeaux et al, 2015;Berg et al, 2010;Crews et al, 2013;Grønli et al, 2014;Lally et al, 2016;Zhu et al, 2015) and parathyroid hormone levels (Bergemann et al, 2008;Rey-Sánchez et al, 2009;Schneider et al, 2000), the latter being negatively correlated to vitamin D. What this review highlights are a multitude of variables that have been found to not significantly correlate with vitamin D within the patient population including but not limited to: BMI, age, gender, smoking, duration of illness and GAF score.…”
Section: Discussionmentioning
confidence: 99%
“…The season of blood sampling was found across 4 included studies to be associated with vitamin D levels in psychotic disorders (Berg et al, 2010;Grønli et al, 2014;Lally et al, 2016;Zhu et al, 2015). This is perhaps not surprising since UVB irradiation intensity varies over the year and it is known that in healthy populations vitamin D levels change with UVB intensity.…”
Section: Discussionmentioning
confidence: 99%
“…It might be that aspects of disease that were omitted in the staging model, such as complications, functional outcome and comorbidity, are of more importance for clinical MDD progression. Indeed some studies showed an association between the pathophysiological dysregulations and suicidal ideation (inflammation 53 and HPA 54 ) and comorbidity (inflammation, 55 HPA 56 and vitamin D 57 ). Finally, we like to acknowledge that different staging models for MDD exist, 58 besides the one we have chosen to use.…”
Section: Discussionmentioning
confidence: 99%
“…Given the broad range of topics covered by the SNOT‐22 questionnaire, as well as the widespread effects of vitamin D, in some ways it is not surprising that a relationship exists between them. For example, numerous reports have shown vitamin D deficiency is associated with poor sleep quality, impaired cognition, and depression . It is also possible that vitamin D may play a role in mucus production in CRS.…”
Section: Discussionmentioning
confidence: 99%